Death and dying of newborns and children: relationships between nursing and family according to Travelbee - Jocellem Alves de Medeiros; José Jailson de Almeida Júnior; Luciane Paula Batista Araújo de Oliveira; Flávia Rayonara Santana da Silva; Clara Caroline dos Santos Silva; Wanessa Cristina Tomaz dos Santos Barros (Associação Brasileira de Enfermagem, 2021)
ABSTRACT Objective: Identify the nursing staff's perception of their relationship with families of newborns and children who are in the process of death and dying. Methods: Qualitative research, carried out in the Neonatal and Pediatric Intensive Care Unit of a public maternity hospital in Rio Grande do Norte, with 17 nursing professionals, through a semi-structured interview. After being transcribed, the data were subjected to Bardin's content analysis and interpreted in the light of the theory of Interpersonal Relations proposed by Travelbee. Results: Four categories emerged from the analysis: "Caring and welcoming people, feelings and stories"; "Reactions in the midst of pain: moving between acceptance and suffering"; "Communication of bad news: challenges and strategies"; "The weight of caring and suffering". Final considerations: Family assistance can be established using Travelbee's principles, as they offer timely theoretical support for nursing actions in the context of the process of death and dying.